2023
DOI: 10.3389/fmicb.2023.1059799
|View full text |Cite
|
Sign up to set email alerts
|

Induced defense strategies of plants against Ralstonia solanacearum

Abstract: Plants respond to Ralstonia solanacearum infestation through two layers of immune system (PTI and ETI). This process involves the production of plant-induced resistance. Strategies for inducing resistance in plants include the formation of tyloses, gels, and callose and changes in the content of cell wall components such as cellulose, hemicellulose, pectin, lignin, and suberin in response to pathogen infestation. When R. solanacearum secrete cell wall degrading enzymes, plants also sense the status of cell wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 126 publications
1
10
0
1
Order By: Relevance
“…In addition to their antimicrobial activity as soluble phenols, HCAAs have also been proposed to crosslink structural polymers in the cell wall during infection, potentially contributing toward the formation of a phenolic barrier that can make the cell wall more resilient to pathogenic degradation ( Zeiss et al, 2021b ). Relatedly, cell wall defenses have been identified as important as inducible barriers against infection and spreading of R. solanacearum ( Shi et al, 2023 ). A recent paper reported that tomato varieties tolerant to virulent strains of R. solanacearum have the ability to restrict bacterial movement and to slow disease progression, thus enhancing apparent resistance to the pathogen ( Kashyap et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to their antimicrobial activity as soluble phenols, HCAAs have also been proposed to crosslink structural polymers in the cell wall during infection, potentially contributing toward the formation of a phenolic barrier that can make the cell wall more resilient to pathogenic degradation ( Zeiss et al, 2021b ). Relatedly, cell wall defenses have been identified as important as inducible barriers against infection and spreading of R. solanacearum ( Shi et al, 2023 ). A recent paper reported that tomato varieties tolerant to virulent strains of R. solanacearum have the ability to restrict bacterial movement and to slow disease progression, thus enhancing apparent resistance to the pathogen ( Kashyap et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ralstonia solanacearum is a Gram-negative soil-borne pathogen with a high destructive capacity, causing bacterial wilt disease and severe crop losses in 310 plant species belonging to 42 families ( Wang et al, 2023 ). However, little is known about the perception of immune elicitors from R. solanacearum ( Shi et al, 2023 ) . A consequence of this is that agricultural approaches, to maintain the bacterial wilt disease, have been limited.…”
Section: Introductionmentioning
confidence: 99%
“…More than 450 species of plants in over 50 families are susceptible to the extremely harmful soil-borne pathogen R. solanacearum. , The host plants for R. solanacearum include a variety of significant commercial crops, such as tomatoes, tobacco, potatoes, and peanut.…”
Section: Introductionmentioning
confidence: 99%
“… 4 More than 450 species of plants in over 50 families are susceptible to the extremely harmful soil-borne pathogen R. solanacearum . 5 , 6 The host plants for R. solanacearum include a variety of significant commercial crops, such as tomatoes, tobacco, potatoes, and peanut. R. solanacearum can cause a wide range of direct crop losses depending on the host, strain, cultivar, land type, and cropping technique.…”
Section: Introductionmentioning
confidence: 99%
“…Para que ocorra a infecção, são necessários cortes nas raízes do hospedeiro, assim, as bactérias movem-se em direção às raízes das plantas por diferentes motilidades, como natação e espasmos, buscando condições favoráveis de crescimento (Shi et al, 2023). Após invadir o sistema radicular do tomateiro, adere às células hospedeiras e desenvolve um biofilme para colonizar o córtex radicular.…”
Section: Introductionunclassified